Natural products targeting regulated cell deaths for adriamycin-induced cardiotoxicity - Zheng Wang; Yanli Zhu; Yu Yao; Wenyu Zhang; Bo Wang; Jing Wang; Yang Yang; Liwen Liu (Cell Death Discovery)
Abstract Adriamycin (ADR), as an anti-cancer drug in routine clinical application, is utilized to treat various cancers such as ovarian cancer, hematological malignant tumor, and endometrial carcinoma. However, its serious dose-dependent cardiotoxicity extremely limits its clinical application. Currently, there remains a dearth of therapeutic agents to mitigate ADR-induced cardiotoxicity. Extensive research has demonstrated that ADR can simultaneously trigger various regulated cell death (RCD) pathways, such as apoptosis, autophagy, ferroptosis, necroptosis, and pyroptosis. Therefore, drugs targeting these RCD pathways may represent effective strategies for treating ADR-induced cardiotoxicity. Natural products, with their wide availability, low cost, and diverse pharmacological activities, have increasingly gained attention. Various natural products, including polyphenols, flavonoids, terpenoids, and alkaloids, can target the RCD pathways involved in ADR-induced cardiotoxicity. Furthermore, these natural products have exhibited excellent properties in preclinical studies or in vitro experiments. This review summarizes the mechanisms of RCD in ADR-induced cardiotoxicity and systematically reviews the natural products targeting these RCD pathways. Finally, we propose future research directions of natural products in this field.